Learning to read critically in teaching and learning - Poulson, Louise; Wallace, Mike, 1950- (Learning to read critically series., 2004)
Combining a teaching text with exemplary reports of research and a literature review conducted by international scholars this collection addresses the critical analysis of texts and the methods used to incorporate such analysis into literature reviews.